Mechanical and histological evaluation of a titanium device for orthodontic anchorage, placed with or without cyanoacrylate adhesive - Anderson Antonio Mamede; Elizabeth Ferreira Martinez; Roberta Tarkany Basting
ABSTRACT Objective: The objective of the present study was to perform a histological evaluation of a titanium mini-implant for orthodontic anchorage. Shear strength and fracture patterns that occurred immediately, 30 and 60 days after insertion with or without N-2-butyl-cyanoacrylate adhesive were evaluated. Methods: Ninety-six mini-implants (Arrow, Peclab, Brazil) were placed in the tibia of 9 male rabbits, with or without an adhesive (Vetbond™, 3M, USA). Histological evaluation was done by optical light microscope. Shear strength testing was performed, followed by fracture analysis with visual inspection. Results: Close contact between the newly formed bone and the device was evidenced in the group without adhesive, whereas gaps in the group with adhesive were found. Tukey test showed similar values in both groups at the immediate time point (20.70 N without adhesive and 24.69 N with adhesive), and higher values for the non-adhesive group, after 30 and 60 days (43.98 N and 78.55 N, respectively). The values for the adhesive group were similar for the immediate time point (24.69 N), 30 days (18.23 N) and 60 days (31.98 N). The fractures were adhesive for both groups at the immediate time point. The fractures were cohesive in bone for the non-adhesive group after 30 and 60 days. Conclusions: The mini-implants showed close bone contact and required higher shear strength for removal at 30 and 60 days for the non-adhesive group. Further studies are needed to assess the proper way to remove the orthodontic anchorage without cohesive fractures in bone.